The Implementation of Physical Education Learning Curriculum 2013 Revised Edition 2016 (Journal of Physical Education and Sports, 2020)
The purpose of this study was to determine the implementation of the 2016 revised edition of the 2016 Physical Education Penjasorkes in Vocational High Schools in Batang District. The research approach used was a qualitative descriptive approach, namely research by providing an overview of facts in the field. The data analysis uses qualitative analysis and percentage quantitative analysis for students. The results of the study for teachers showed that the results of the planning study was well, there were 17 or (89%) of the teachers implemented lesson plans, and 3 did not; from the implementation, 14 or (74%) of the teachers implemented scientific learning and 5 did not implement science; from the results of the learning evaluation it is known that 14 or 74% of teachers carry out authentic assessments. But only 3 assessments are affective, psychomotor, and cognitive, while 5 other teachers make authentic assessments, but do not carry back to the old assessment rubics. For students divided into 2 aspects: knowledge of the curriculum 2013 and student responses. In the first stage student knowledge was obtained 24 (11.2%) very good, 171 (71.3%) good; 41 (71.3%) were quite good; 1 (0.4%) less. In the second stage, 77 students' responses (32.1%) were very good; 152 (63.3%) are good, 11 (4.6%) are lacking, so a good average is obtained. Suggestions that researchers can give related to the results of the research are that before implementing the curriculum each school reports school readiness such as facilities and infrastructure are improved and the readiness of the principal or teacher reports to the local service so that the government knows and evaluates the implementation of the latest curriculum.